2017
DOI: 10.1186/s13030-017-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect for Japanese workers of a self-help computerized cognitive behaviour therapy program with a supplement soft drink

Abstract: BackgroundComputerized cognitive behaviour therapy (CCBT) programs can provide a useful self-help approach to the treatment of psychological problems. Previous studies have shown that CCBT has moderate effects on depression, insomnia, and anxiety. The present study investigated whether a supplement drink that includes L-carnosine enhances the effect of CCBT on psychological well-being.MethodsEighty-seven participants were randomly allocated to a control group, CCBT, or CCBT with supplement drink. The CCBT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…We thought important to remind the reader about the context in which this experimental research took place, given the high threat to internal validity caused by the well documented investigators’ bias as well as the subjects’ and participation biases [ 2 4 ], making the quality of this study low as per the Cochrane Risk of Bias Tool for Randomized Controlled Trials ([ 5 ], Table 8.5.d). More precisely, in Shirotsuki et al’s study [ 1 ], we found a high risk of bias in selective reporting, incomplete outcome data, and blinding of participants and outcome assessment, meaning that conclusions of such low quality studies must be cautiously taken.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We thought important to remind the reader about the context in which this experimental research took place, given the high threat to internal validity caused by the well documented investigators’ bias as well as the subjects’ and participation biases [ 2 4 ], making the quality of this study low as per the Cochrane Risk of Bias Tool for Randomized Controlled Trials ([ 5 ], Table 8.5.d). More precisely, in Shirotsuki et al’s study [ 1 ], we found a high risk of bias in selective reporting, incomplete outcome data, and blinding of participants and outcome assessment, meaning that conclusions of such low quality studies must be cautiously taken.…”
mentioning
confidence: 78%
“…Nevertheless, these limits remain highly threatening to the internal validity and our questions relative to what looks like serious methodological shortcomings should lead to only one conclusion: the study of Shirotsuki, et al [1] should be re-conducted before any valid conclusion could be drawn.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two interesting trials have examined the effects of carnosine on various aspects of behaviour, literacy-related skills, and mood. A Japanese trial in 87 healthy office workers [195] showed that a supplement drink containing carnosine (200 mg daily) along with a computerized cognitive behavioural therapy program reduced self-reported tension and anxiety compared to the placebo. Another RCT in Finland investigated the effects of a supplement containing carnosine on literacy-related skills in children [196].…”
Section: Human Randomized Controlled Trials Of the Role Of Carnosimentioning
confidence: 99%
“…Only two weeks of supplementation with L-histidine (1.65 g daily) improved fatigue scores in men with chronic fatigue syndrome [173]. Similarly, two weeks of supplementation with another carnosine precursor, β-alanine, improved resistance against fatigue during sustained military operation in recreationally active adults [175] and a drink containing carnosine together with a computerized cognitive behavioural therapy program reduced self-reported fatigue in office workers [195].…”
Section: Human Randomized Controlled Trials Of the Role Of Carnosimentioning
confidence: 99%